Aripiprazole Once-Monthly in the Treatment of Acute Psychotic Episodes in Schizophrenia: Post Hoc Analysis of Positive and Negative Syndrome Scale Marder Factor Scores. Issue 3 (June 2017) - Ismail, Zahinoor; Peters-Strickland, Timothy; Miguelez, Maia; Baker, Ross A.; Hertel, Peter; Eramo, Anna; Jin, Na; Perry, Pamela; Sanchez, Raymond; McQuade, Robert D.; Kane, John M.
Abstract: Background: Long-acting injectable antipsychotics are treatment options for acute and long-term treatment of patients with schizophrenia. In a previously published 12-week randomized, double-blind, placebo-controlled clinical trial of patients with schizophrenia experiencing an acute psychotic episode, aripiprazole once-monthly 400 mg (AOM 400) produced significantly greater improvement than placebo on the primary endpoint, Positive and Negative Syndrome Scale (PANSS) total score at week 10. Methods: To examine the efficacy of AOM 400 across a broader representation of schizophrenia symptoms, including agitation, a post hoc analysis of this trial was carried out to assess the change in PANSS Marder factor domains (positive symptoms, negative symptoms, disorganized thought, uncontrolled hostility/excitement, and anxiety/depression) and the PANSS excited component (equivalent to Marder factor domain uncontrolled hostility/excitement plus the tension item) by comparing differences in change from baseline between AOM 400 and placebo using a mixed model for repeated measures. Results: The differences between treatment and placebo for all factors were statistically significant, with improvements seen as early as week 1 or 2, and maintained through week 12. Thus, AOM 400, supplemented with oral aripiprazole in the first 2 weeks, showed significantly greater efficacy versus placebo in acutely ill patients with schizophrenia in all 5 Marder illness domains, as well as in agitation as conceptualized by the PANSS excited component score. Conclusions: These findings indicate that AOM 400 is efficacious across the spectrum of schizophrenia symptoms in acutely ill patients, with implications for both short-term and, by extension, long-term patient outcomes.